The gifting logos : expertise in the digital commons - Hartelius, E. Johanna, 1979- (University of California Press, 2020)
"The Gifting Logos: Expertise in the Digital Commons provides an extensive analysis of knowledge and creativity in twenty-first century networked culture. Analyzing massive projects like the Wayback Machine, the Internet Archive, and the Creative Commons Licenses, The Gifting Logos responds to a fundamental question, What does it mean to know something and to make something? With the idea of a gifting logos, Hartelius integrates three habits of a rhetorical epistemology: the invention of cultural materials such as text, images, and software; the imbuing or encoding of the materials with the creator's experience; and the constitution and dissemination of the materials as gifts"--